An empirical retrospect of the impacts of government expenditures on economic growth: New evidence from the Nigerian economy - Stephen T. Onifade; Savaðs Çevik; Savaðs Erdoægan; Simplice Asongu; Festus Victor Bekun (African Governance and Development Institute (AGDI), 2019)
The impacts of public expenditures on economic growth have been revisited in this paper with respect to capital expenditure, recurrent expenditure and the government fiscal expansion in line with support for the budgetary allocations to various sectors in the context of the Nigerian economy. The Pesaran ARDL approach has been applied to carry out the impact analysis using annual time series data from 1981 to 2017. Empirical findings support the existence of a level relationship between public spending indicators and economic growth in Nigeria. Incisively, recurrent expenditures of government were found to be significantly impacting on economic growth in a negative way while the positive impacts of public capital expenditures were not significant to economic growth over the period of the study. Further results from the granger causality test reveal that fiscal expansion of the government that is hinged on debt financing is strongly granger causing public expenditures and domestic investment with the latter also granger causing real growth in the economy. We, therefore, provide some important policy recommendations following the results of the empirical analysis.
Keywords: 330; Nigeria; Fiscal policies; Economic Growth; Debt to GDP ratio; ARDL Models